Vivências das mulheres da etnia Atikum na agricultura e para além dela: uma etnografia de memórias, histórias e experiências - Paulo, Elizabete Oliveira de Sá (Universidade Federal de São Carlos, 2025)
This work presents the narrative and a detailed account of the life of an indigenous Atikum woman, and her relationships with other women, with the land, with agriculture and beyond, or the mere production of food, from her childhood in the village to her adult life at university. Through her personal experience and her reflections on them, the author outlines an overview of the culture, challenges and struggle to preserve the indigenous Atikum identity. This work was developed with the participation of some women who live in the Aldeia Sede and surrounding areas in Pernambuco, through a questionnaire with objective and clear questions, which were sent and answered through WhatsApp messages. The data were collected over the weekends, through written and voice recordings, allowing the participants to answer the questions comfortably and without rushing. Some of the key points presented were: the connection with the land and its centrality in the life of the community and the Atikum identity, especially of women; the importance and some of the ways in which traditional and, more recently, academic knowledge is transmitted; some challenges faced throughout history by the community, such as the loss of land, the imposition of a different culture and discrimination, and, on the other hand, the overcoming of these challenges to keep the Atikum culture and identity alive; the role of women in the community, both in agricultural activities and in the preservation of culture; the intersectionality between gender, ethnicity and social class, showing how indigenous women face specific challenges. The research aimed to present a testimony of the life and culture of an Atikum community based on the experience of a woman from this ethnic group and made it possible to understand the importance of land, culture, the role of women and resistance for indigenous identity. The work is also an invitation to reflect on the importance of valuing and preserving cultural diversity and the rights of indigenous peoples.
Experiences of Atikum women in agriculture and beyond: an ethnography of memories, stories and experiences
Keywords: Mulheres Indígenas Atikum; Agricultura; Resistência cultural; Ciências Sociais; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA